POA : building SOA from the ground up moving process to the forefront. - Sadler, Shone
As technologists today, we face a uniquely challenging paradox. On the one hand, Web services have created renewed excitement for service-oriented architectures (SOA) as the answer to common integration problems; on the other hand, today's application platforms (J2EE & .NET), used to implement SOA applications, are often deemed overly complex and a barrier to widespread SOA adoption. While the primary goal of the industry is to make the concepts and benefits of SOA mainstream, we must recognize that SOA itself must evolve to facilitate such widespread adoption. Fundamentally, we must move from focusing on the integration aspects of SOA (the "band-aid") to focusing on how to build applications based on the principles of SOA (the solution): that is, applications that are inherently interoperable. In this article we discuss how the convergence of several key technologies is essential to taking SOA mainstream, and how process oriented architectures (POA) are evolving to meet this need by providing a more detailed version of SOA that derives its fundamental purpose from a process-oriented view of application development.